Entomophagy as Local Wisdom and a Strategy for Food Security: Insect Consumption Practices in Gunungkidul, Indonesia - Hermawan, Hary; Fuadi Afif (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2026)
This study examines the practice of entomophagy (insect consumption) among communities in Gunungkidul, Indonesia, as a manifestation of local wisdom and a strategy for sustainable food security. Although insects are globally recognized as an efficient and environmentally friendly future protein source, psychological barriers such as disgust and food neophobia remain significant obstacles to the adoption of entomophagy in many non-traditional societies. This research employs a Critical Literature Review approach by analyzing scholarly works from scientific databases such as ScienceDirect and Scopus, interpreted through Pierre Bourdieu’s theory of cultural capital. The findings reveal that entomophagy in Gunungkidul has been internalized as a habitus transmitted across generations (embodied cultural capital), subsequently transformed into objectified capital in the form of culinary commodities and local souvenirs, and further legitimized as institutionalized capital through recognition within the regional tourism sector. From a nutritional perspective, local insect species such as the grasshopper (Valanga nigricornis) contain crude protein levels of up to 27.86 g per 100 g, contributing significantly to addressing local nutritional gaps. In conclusion, entomophagy in Gunungkidul is not merely a subsistence practice but represents a form of cultural distinction that reinforces food security while offering potential for gastronomic tourism development. This study recommends the need for regulatory support and innovation in invisible insect-based food products to enhance broader market acceptance in the future.